Scholarly communication and discontentments with it - Codina, Lluís (Anuario ThinkEPI, 2023)
This is a review of the essential characteristics of scholarly communication and an examination of the main criticisms of the system of evaluation of science based on publications. Expressions such as "pressure to publish" or "perish or publish" are critically examined, and it is argued that such framings do not correspond to an identifiable state of affairs in the case of Spanish science and universities. We also review the reasons for this discontent, which is due to the existence of a small group of publishers with great economic influence that apparently operate with excessive profit margins.
Keywords: Scholarly commuication; Science evaluation; Scientific journals; Presure to publish; Perish or publish!